Exploring factors that influence the meaning of grades to sophomores in College of Home Economic, University of the Philippines Diliman - Aquino, Paulina Bianca N.; Daez, Jennifer Roxanne S.
The study aimed to identify what grades mean to sophomore students in CHE UPD, what factors contribute to how they give meaning to the grades they receive and if they consider grades important to them. Being a qualitative research which used the exploratory approach, interviews were conducted and results from male and female respondents were analyzed separately to see if gender was of relation to influences. It was found out that the meanings of grades were mostly related to school. From all the factors identified, familial factors remain to have the most influence both for male and female respondents. For the last objective of the study, grades for the sophomores remain to be an important aspect in one's academic life.